Imaginaries - Michel Porret (Scienza & Politica)
The essay analyses the epistemological status of the notion of the social imaginary as it developed in French culture and in the thought of Bronislaw Baczko. The centrality of this notion is punctually traced and highlighted in all Baczko’s works, both those more directly dedicated to symbolic history and those devoted to the Enlightenment and revolutionary practices.